Acute vision loss in post-partum period as presenting symptom of HIV-associated cryptococcal meningitis–an unusual case report. Issue 1 (December 2016) - More, Aniruddha; Garg, Ravindra; Malhotra, Hardeep; Kumar, Neeraj; Uniyal, Ravi
Abstract Background Acute vision loss in the post-partum period can occur due to many reasons. Eclampsia, posterior reversible encephalopathy syndrome (PRES), pituitary apoplexy, and central serous retinopathy are some of the important causes. Cryptococcal meningitis as a cause of acute vision loss in the post-partum period has not been mentioned in literature. Case presentation A 25-year-old female presented to us with acute bilateral complete vision loss in the post-partum period. Her serum was tested positive for HIV antibodies. Cerebrospinal fluid (CSF) examination revealed cryptococcal meningitis. She was started on amphotericin B, antiretroviral drugs, and steroids. Though symptoms of meningitis resolved after treatment no significant improvement in vision was observed at 3 months. Conclusions Cryptococcal meningitis may be considered as one of the causes of acute vision loss in pregnant/post-partum females with human immunodeficiency virus (HIV) positivity.